Spliceosome assembly involves the binding and release of U4 small nuclear ribonucleoprotein. - Lamond, A I (1988)
Splicing complexes that form a rabbit beta-globin precursor mRNA (pre-mRNA) have been analyzed for their small nuclear RNA (snRNA) content by both affinity chromatography and specific probe hybridization of replicas of native electrophoretic gels. A pathway of spliceosome assembly was deduced that has at least three stages. (i) U2 small nuclear ribonucleoprotein (snRNP) alone binds to sequences of mRNA upstream of the 3' splice site. (ii) U4, U5, and U6 snRNPs bind, apparently simultaneously. (iii) U4 snRNP is released to generate a spliceosome that contains U2, U5, and U6 snRNPs together with the RNA intermediates in splicing. U1 snRNP was not detected in association with any of these complexes. A parallel analysis of the spliceosome found with an adenovirus precursor mRNA substrate yielded an identical snRNP composition with one additional, unidentified RNA species, called X. This latter RNA species was not detected in the spliceosome bound to the beta-globin substrate.